2020
DOI: 10.1039/d0dt02424d
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear phosphorescent rhenium(i) complexes as potential anticancer and photodynamic therapy agents

Abstract: Chemotherapeutic agents that affect lysosomal functions represent a promising strategy for selective tumor therapy and overcoming drug resistance. In this work, two dinuclear phosphorescent rhenium(I) tricarbonyl complexes (DRe1 and DRe2)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…In compounds 10 and 11 , carboline derivatives were employed as equatorial ligands (Figure 3). [38] Both compounds appeared to localize to lysosomes. Complex 11 was found to cause lysosome damage in A549 cells, owing to its ability to produce reactive oxygen species (ROS) like superoxide (O 2 .− ) and hydrogen peroxide (H 2 O 2 ).…”
Section: Homonuclear Complexesmentioning
confidence: 98%
“…In compounds 10 and 11 , carboline derivatives were employed as equatorial ligands (Figure 3). [38] Both compounds appeared to localize to lysosomes. Complex 11 was found to cause lysosome damage in A549 cells, owing to its ability to produce reactive oxygen species (ROS) like superoxide (O 2 .− ) and hydrogen peroxide (H 2 O 2 ).…”
Section: Homonuclear Complexesmentioning
confidence: 98%
“…They exhibited significant phototoxicity under blue-light irradiation, producing ROS that resulted in lysosomal damage. The rhenium(I) β-carboline complexes (RE7) had higher 1 O 2 yields under acidic conditions, which are expected to facilitate cancer targeting [100]. The gold(II)/rhenium(I) heterodinuclear complexes (Figure 12:RE8) that have also been produced benefit from the gold delivering increased cytotoxicity to the strongly fluorescent rhenium complexes.…”
Section: Rhenium Complexesmentioning
confidence: 99%
“…Table 4. A summary of the IC 50 values, luminescent properties and special features of rhenium(I) luminescent complexes: phosphine ligated complex RE1 [93], GHS-responsive bio-sensing complex RE2 [94], mitochondrial-targeted theragnostic complex RE3 [96], rhenium(I) aqua complex RE5 [98], heterodinuclear Re(I) β-carboline complex RE7 [100], and gold(II)/rhenium(I) heterodinuclear complex RE8 [102]. , GHS-responsive bio-sensing complex RE2 [94], mitochondrial-targeted theragnostic complex RE3 [96], β-carboline rhenium complex RE4 [97], rhenium(I) aqua complex RE5 [98], apoptosis-ferroptosis dual-induction complex RE6 [99], heterodinuclear Re(I) β-carboline complexes RE7 [100], and gold(II)/rhenium(I) heterodinuclear complex RE6 [102].…”
Section: Rhenium Complexesmentioning
confidence: 99%
“…The complexes Dre1 and Dre2 showed a significant photocytotoxicity toward A549 cell lines giving IC 50 values of 0.26 and 0.11µM, respectively, compared to 8.3µM for cisplatin. The authors suggested that these complexes may be used as potential anticancer and PDT agents (138).…”
Section: Rheniummentioning
confidence: 99%